CONDITION OF PERIODONTAL TISSUES IN CHILDREN WITH BRONCHIAL ASTHMA - Avdeev, O.V.; Vydoinyk, O.Ya.; Hevkalyuk, N.O.; Posolenik, L.Ya.; Hrad, A.O. (World of Medicine and Biology, 2019)
The article presents the results of the periodontal tissues status assessment in children with asthma compared to children without concomitant somatic diseases, the status of periodontal tissues and oral hygiene in children monitoring groups. The above processes can be explained by the influence of somatic pathology.
Keywords: children; gingivitis; asthma; periodontal disease; caries; indices; periodontal tissues